Predictors of Hospital Stay in Children with Acute Gastroenteritis and Dehydration - Muhammad Aamir Aziz, Mehwish Alamdar, Sughra Wahid, Afsheen Asghar Khan, Perwez Ali, Mahvish Iqbal, Ahmad Yar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Acute gastroenteritis with dehydration is a leading cause of pediatric hospital admissions. Identifying predictors of prolonged hospital stay may improve clinical outcomes and optimize resource utilization. Objective: To determine clinical and laboratory predictors of hospital stay among children admitted with acute gastroenteritis and dehydration. Methodology: This was a hospital-based cross-sectional analytical study conducted at Paediatrics Department of Sahiwal Teaching Hospital, Sahiwal from August 2022 to January 2023. A total of 310 children admitted with acute gastroenteritis and clinical dehydration were enrolled in the study. Results: Out of 310 children, 128 (41.3%) had prolonged hospitalization. These children were younger (2.9 ± 2.3 vs 4.6 ± 2.9 years), had lower weight (11.4 ± 3.7 vs 13.6 ± 4.2 kg), and higher malnutrition rates (43.8% vs 20.9%) (p≤0.01). Severe dehydration (40.6% vs 8.8%), lethargy (60.9% vs 22.0%), oliguria (56.3% vs 14.3%), and tachycardia (133 ± 19 vs 118 ± 14 bpm) were significantly more common (p<0.001). Laboratory abnormalities included lower sodium (136.5 ± 6.1 mEq/L), higher urea (45.7 ± 15.8 mg/dL), elevated creatinine (0.73 ± 0.23 mg/dL), and metabolic acidosis (48.4%) (p<0.001). Intravenous fluids were required in 89.1% of prolonged cases. Severe dehydration (OR 4.82), IV fluid requirement (OR 5.96), malnutrition (OR 2.76), hypernatremia (OR 3.45), and delayed presentation (OR 2.57) independently predicted longer stay. Conclusion: Prolonged hospitalization is primarily driven by dehydration severity and metabolic derangements. Early risk stratification and prompt rehydration may significantly reduce hospital stay and improve outcomes. Keywords: Acute gastroenteritis, dehydration, pediatric hospitalization, length of hospital stay, predictors, electrolyte imbalance.